The Reality of Implementing E-Management in Light of Knowledge Management Operations from Principals Point of view at Al-Zarqa First Directorate - Almaaitah, Nawal Zaal Mohammad (Journal of Educational and Psychological Sciences, 2021)
This Study aimed to identify The Reality of Implementing E-Management In Light of Knowledge Management Operation from Principals Point of view at Al-Zarqa First Directorate, and to determine the effect of variables (sex, and years of experience), the researcher used the Descriptive approaches, to collect data Questioner used which consisted from (34) paragraph , study population consisted of all principal in Al- first Zarqa directorate (152) Female and male, the sample consist from (59) Female and (49) male, chosen randomly, the result of SPSS analysis shown that the level of Implementing E-Management In Light of Knowledge Management Operation from Principals Point of view at Al-Zarqa First Directorate was very high with total average (4.25 out of 5) and at the level of dimensions The knowledge acquisition dimension attained the highest average (4.83), then the knowledge storage dimension with an average (4.43), the third after knowledge generation with an average (4.25), all of which were rated (very high), and the fourth after knowledge transfer with an average (4.11), and the fifth after knowledge application with an average (4.10). The knowledge-sharing dimension has an average of (3.81), and the last three are (high). The finding also showed there was no statistically significant differences at (α≤0.05) refer to principal sex (male and female) in addition there were statistically significant differences between the principals years of experience in favor of (10 years and more). Based on the results, the researcher presented a number of recommendations and proposals, to enhance the reality of applying electronic management in light of knowledge management processes in public schools in Zarqa, the whole of the Kingdom and the Arab countries.
Keywords: E-Management Applying; Knowledge Management Operations; School Principals Opinions; Al-Zarqa First Directorate; Jordan